Remembering the Founding of the Journal of Gender and Law - Fredrickson, Caroline (Columbia Journal of Gender and Law, 2016)
In my first year of law school, I felt baffled by the experience of legal education. I had spent three years working in politics—in campaigns and on Capitol Hill—and had entered law school to find a way to add intellectual depth to my instinctive progressive beliefs. But what I found, I perceived to be arid and counterfactual, with caselaw divorced from political context and history that had led legislators and judges to reach particular decisions. I was discouraged and briefly thought I had made a wrong turn on my life path, until I found a group of friends in the same intellectual and spiritual funk.1Together we decided to found a new journal, which became the Journal of Gender and Law (JGL). Founding the Journal was a real starting point for me in thinking about gender, sexuality, economic empowerment, and racial justice as overlapping and yet distinct lenses through which to view the law. The group of students who came together shared the feeling that law school was a somewhat strange and alienating environment and didn’t seem to provide us with what we were seeking. So we set out to fill that gap ourselves, resulting in the underlying philosophy of JGL: an interdisciplinary approach to the problems that continue to confound our society in terms of gender and race and the simultaneous disadvantages that affect women of color. As Justice Ruth Bader Ginsburg wrote in her introduction to our first issue, the Columbia Journal of Gender and Lawsought to “portray today’s feminist movement, not as unitary, rigid or doctrinaire, but as a spacious home, with rooms enough to accommodate all who have the imagination and determination to work for the full realization of human potential.”